Airsense - Low-Cost Indoor Air Quality Monitoring Wireless System - Marques, R. (2025)
This manuscript presents the project aimed at creating a low-cost indoor air quality monitoring system. By using a variety of sensors connected to an ESP32 microcontroller, the system measures specific parameters such as carbon dioxide, volatile organic compounds, particulate matter, temperature, humidity, and pressure. The sensor-recorded measurements are sent to an InfluxDB database via Wi-Fi, where they are accessed by Grafana, which generates a graphical user interface that displays the evolution of all collected data. The values can be visualized in various graphical styles according to the user’s preference, including tables, time-series charts, and histograms. Initially, some research was conducted to evaluate various types of microcontrollers and sensors to select the best options based on factors such as cost, size, and measurement accuracy. A printed circuit board and a 3D-printed enclosure were designed alongside the final prototype, which facilitated the integration of the various hardware components. Lastly, a two week-long test was conducted, in a school environment, using the final hardware to validate the overall results and operating behavior of the developed system.